Investigating the competitive intelligence practices of Peruvian fresh grapes exporters - Bisson, Christophe (2018)
This paper reports an empirical study of Peruvian fresh grapes exporters with the aim of delineating the behavioral and operational typology of their competitive intelligence practices. Cluster analysis was used as an exploratory tool to determine the correlation, if any, between the size of the company, grapes exports share of total exports, the percentage of the Red Globe variety in total grapes exports and the size of the grape farm with the typology and the average price received at export between August 2016 and July 2017. The behavioral and operational typology of competitive intelligence practices model, developed by Wright et al, (2012), was used. The findings reveal that exporters have a positive behavior towards competitive intelligence practices, but cannot make good use of them due to a lack of knowledge, and deficiencies in organization and in technological and IT systems support. As 37 companies participated in this experiment, this study could be extended to all non-traditional Peruvian agricultural exports. It has been possible to identify areas where changes are needed to enable these exporters to perform at a higher level of competence. In addition, it appeared that a slightly higher level of attitude and IT systems support pays off as medium-sized companies achieved a higher price per ton compared to big companies. This study is the first to present a typology of competitive intelligence practices in Peru and is one of the very first to study competitive intelligence in this country and agriculture.